Soil loss due to water erosion in the Estibaná River sub-basin, Panama - Castro-Villarreal, Jorge Alberto (2024)
Introduction. Soil degradation develops naturally on a small scale; however, human intervention has accelerated and maximized this process. Erosion is one of the main processes linked to degradation; this, combined with exploitation systems not adapted to the environment, is the basis for the reduction of productivity and pollution of water bodies. In Panama, soil degradation affects 20,787 km2, an area that covers zones where much of the country’s agricultural production is concentrated. Objective. To determine soil loss due to water erosion in the Estibana River sub-basin through the implementation of erosion plots. Materials and methods. The research was carried out in the Estibana River sub-basin, province of Los Santos, Azuero Peninsula, Panama (Arco Seco), during the rainy season (May-December) of the years 2020 and 2021. The methodology of erosion plots was applied, using a random complete block design in three locations, evaluating three treatments, with three repetitions, where total runoff, mass of transported sediments (suspended and precipitated), and a multifactorial analysis of variance was performed. Results. Erosion was influenced by factors such as slope, soil cover and precipitation. It was determined that erosion amounted to 62.98 Mg/ha/year in bare soil on 10 % slopes. Introducing living barriers and soil cover mitigated erosion damage. The behavior on other slopes was similar. Conclusions. The variation in the frequency, intensity and duration of precipitation, as well as anthropogenic interventions in the natural environment, are the main causes of the increase in soil loss within the Estibana River sub-basin. The implementation of low-cost conservation efforts can mitigate the erosive effect of surface runoff.